The Influence of the Nuclear Shadowing Effect on Astrophysical Neutrino Flux - Z. Y. Liu; H. Y. Yang; Y. G. Zheng; C. Y. Yang (The Astrophysical Journal, 2025)
The production of neutrinos from ultrahigh-energy cosmic rays (UHECRs) is modulated by nuclear shadowing effects that are often overlooked in theoretical models. Nuclear shadowing, the suppression of pion production in photonuclear interactions within heavy nuclei, plays a critical role in determining neutrino yields. Current predictions frequently assume that UHECRs are proton-dominated and neglect the nuclear medium’s influence on pion cross sections, leading to overestimates of neutrino fluxes. Here, we incorporate nuclear shadowing effects into simulations of proton–photon ( pγ ) and proton–proton ( pp ) interactions in astrophysical source environments. We also account for nuclear photodisintegration in pγ processes, which further modifies secondary particle production. We integrate these effects into pure composition scenarios ( p , He, N, and Fe) to calculate the resultant neutrino background flux. Our results demonstrate that nuclear shadowing can reduce neutrino fluxes from heavy nuclei by a factor of 2–3 compared to proton-only scenarios.